Breast cancer in Sarawak, Borneo—A decade of screening programmes - Melissa Lim, Siaw Han; Shirley Tan, Siang Ning; Juriah, Sulehan; Nafeesa, Mat Ali; Mohamad Adam, Bujang; Yolanda, Augustin (John Wiley & Sons, Inc, 2024)
Background and context: Sarawak, the largest state in Malaysia with a population of 2.9 million and 45% of them living more than 100 km away from urban cities. These communities are at risk of delayed diag-nosis and advanced diseases due to limited access to healthcare ser-vices. We have only one tertiary government hospital equipped with both radiotherapy and chemotherapy facilities and 4 government hos-pitals with mammogram facilities. Aim: Sarawak Breast Cancer Support Group (SBCSG) is a local NGO registered with the Registrar of Societies in August 2000. Since 2012, SBCSG spearheaded the breast cancer early detection and screening outreach programme all across Sarawak, with a special focus on those living in rural areas. This paper describes results from our 10-year programme. Strategy/tactics: These programmes were organized or co-organized by SBCSG from 2013 to 2023. At each site, local organizers, including community leaders and the ministry of health (MOH) were involved in the outreach planning. Women of age 18 years and above were invited. Programme/Policy: The Malaysian Clinical Practice Guidelines 2019 (CPG) for breast cancer management recommended clinical breast examination (CBE) for women age 35 and older and the use of mam-mogram depending on individual risk factors. However, the uptake of mammograms among Malaysian women remains low, ranging from 7% to 30% of the target population and there is no recorded data from Sarawak. Process: A1–2 day breast camp was set up at each site, staffed by volunteer nurses and doctors from SBCSG and MOH personnel. Here, participants were registered and explained about the camp proce-dures. Demographic, risk factors, family history and clinical breast examination findings were obtained. Women with abnormal findings were referred to the nearest clinic or hospital for further management. Outcomes: We have screened 2050 women with mean(SD) age of 44.7 (15.4) years old, with 7.1% of them exhibited abnormal findings, predominantly identified as lumps (96.6%). Urban screening sites reported abnormal findings in 9% (85/949) of women compared to 5% (61/1101) in rural sites. Bidayuh ethnic group was found with the highest abnormal findings (28.6%), followed by Chinese (27.2%) andMalay (19.0%). Women with fewer than 3 children were more likely to exhibit abnormal findings [8.3% (85/1021) vs. 5.9% (61/1029); p = 0.003]. Using multivariate analysis, site was found to be the most important factor. Subjects who were screened at urban sites were 1.6 times more likely to have abnormal findings. Additionally, those between age 30 and 59 years old were 2.3 times more likely to have abnormal findings compared to the older group. What was learned: The primary independent variable is screening site, which points to the potential impact of lifestyle in abnormal findings. Women in rural areas tend to have more children, a trend that can be attributed to socioeconomic and cultural norms. The higher incidence of abnormal findings in urban areas highlight the need for increased awareness in urban areas.